Epidemiology of Herpes Simplex Virus Infection in Pregnancy: A Pilot Study - A. Bellizzi Ph.D; D. Fioriti; V. Marcone; E. Anzivino; M. Mischitelli; V. Barucca; A. Parisi; E. Moreira; J. Osborn; F. Chiarini; E. Calzolari; V. Pietropaolo (European Journal of Inflammation, 2009)
Herpes simplex virus (HSV) infection is one of the most common sexually transmitted viral diseases worldwide. HSV type 2 causes most genital herpes and HSV type 1 is usually transmitted via non-sexual contacts. We studied 109 pregnant women between January 2007 and December 2008, in relation to their age, condom use, number of sexual partners, age at first intercourse, parity and smoking habits. The aim of this study is to evaluate the prevalence of HSV cervical infection and HSV co-infection with other genital microorganisms associated with poor neonatal outcome. Our results show that of the 109 outpatients enrolled, 30% were HSV1 and/or HSV2 positive, of whom 30% were infected with both HSV1 and HSV2, 18% were infected with HSV1 alone and 52% with HSV2 alone. A significant association between HSV1 and HSV2 infection was found, and the prevalence of HSV2 infection in women infected with HSV1 was 63%. The prevalence of HSV1/2 varied in the presence of other vaginal microorganisms but a statistical significant association was not found. This pilot study is probably too small to obtain statistically significant results. Nevertheless, using these observed results, we calculated that about 530 patients with comparable features should be enrolled to detect an increase of 50% in HSV infection due to the presence of other genital infections and potential risk factors.